(untitled) (Journal of Agriculture and Environment, 2015)
The effect of global climate change in Nepal could be observed by glacier retreat in the Himalaya region and change in the pattern of the south west monsoon which is the only reliable source of water for farming. Climate change has been occurred in Terai, hills and mountain of Nepal resulting change in agriculture systems leading to the emergence of new insect, pest and disease of crops and animals. There are frequent losses of lives, crops and, human settlements due to occurrence of flash floods, droughts, typhoon and hurricanes in the world mainly due to climate change. Global food production and trade have been affected by the negative consequences of climate change as a result countries like Nepal are also victimized due to the negative effect of climate change. Increase in C02concentration in the atmosphere and change in precipitation are being the main cause of floods, droughts, glacier retreat, and melting of snows, hence, change in the flora and fauna globally. To address such measures of climate change, Nepal has been trying to develop some adoptive ways such as development of climate resilient technology including crop varieties, animal breeds; agronomic practices that could address vagaries of climate change and sustain food and nutritional security. In Nepal, the effect of climate change is more pronounced in hills and mountains with respect to increase in temperature than that of Terai. This paper tries to address issue of global climate change with respect to food security of Nepal by applying some of the pragmatic adoptive measures to follow in agriculture for sustaining food security in Nepal.